ANALYSIS OF EFFICIENT CARRY SELECT ADDER USING BRENT KUNG ADDER - S., Udhayaprakash (International Journal of Psychosocial Rehabilitation, 2017)
Adders are the basic building blocks in a digital circuit design. It is used to perform the additions of two n-bit numbers. Adders find its applications in areas like microprocessor, digital signal processing and even in data path logic operations. Performance of a circuit is mainly determined by the speed of addition. To perform fast arithmetic operations, high speed adders combined with parallel prefix adder architectures are used. Instead of using Ripple Carry Adder (RCA), here a parallel prefix adder i.e. Brent Kung (BK) adder is used with carry select adder for obtaining better performance. The Brent Kung adder offers the best performance when compared with the other parallel prefix adders and it reduces the delay of a conventional RCA. Four architecture structures namely Regular Linear BK CSA, Regular Modified BK CSA, Regular SQRT BK CSA and Modified SQRT BK CSA are designed so as to analyze and to compare the performance in terms of area, power and delay. From the analysis, it is clear that modified SQRT Brent Kung Carry Select Adder gives better results than other adder architectures. The designs have been simulated using Tanner EDA tool.